Research on the evolution mechanism of main control factors for coalbed methane extraction - Ting Xia; Enyu Xu; Xijian Li; Shoukun Chen (PLoS ONE, 2026)
To study the isothermal adsorption and desorption diffusion processes of anthracite, isothermal adsorption and desorption experiments of coal powder were conducted, and numerical simulations were carried out using COMSOL Multiphysics. The results showed that the DR equation had the best fitting effect on the gas adsorption curve, followed by the Langmuir equation, and the BET equation had the worst fitting effect, with R 2 values of 0.9986, 0.9976, and 0.9765, respectively. The potential reason for this is the development of micropores in anthracite, with a relatively large proportion of gas molecules are primarily adsorbed in micropores; The single-pore model is suitable for fitting the gas adsorption process, but not for fitting the gas desorption process. Taking into account the spatial and temporal evolution characteristics of the gas diffusion coefficient, the dual-pore model is more suitable for simulating gas migration at the coal seam scale; Gas adsorption can cause expansion and deformation of the coal matrix, and some molecular scale pore throats have smaller pore throats than gas molecules after adsorption and expansion, resulting in a blocking effect on gas molecules in the pores. Therefore, the amount of gas desorption is usually smaller than the adsorption amount; There are specific differences between gas adsorption and desorption processes. Gas adsorption is a constant volume condition, while desorption is a constant pressure condition. Therefore, adsorption and desorption cannot be simply regarded as reversible processes. The research results provide theoretical support for a deeper understanding of the processes and mechanisms of gas adsorption-diffusion and desorption-diffusion.